Festa e morte: Experimentação de Prokófiev com Eisenstein na cena colorida de Ivan, o terrível (Orfeu, 2025)
Analysis of the colour sequence of Ivan the Terrible, Part 2, by Sergei Eisenstein, with music by Sergei Prokofiev, showing the importance of experimentation in the composition process – both of the scene and of the music. Free experimentation occurs mainly in the use of interchangeable modules, written by Prokofiev and used freely in the montage.